Blade runner and literature - Sallai Krisztina (2005)
The aim of this diploma work is to prove the thesis that the film Blade Runner can be understood only through the knowledge of literary works like: the Bible, John Milton's Paradise Lost, and William Blake's America: a Prophecy. As an additional topic I will include the theme "legends", especially the legend of the unicorn, to the work so as to help to understand the message of the film. My goal is to try to compare the works mentioned with the film so as to clarify my thesis. Namely, that Deckard is a replicant who can be identified with the biblical Adam, while Eve is Rachael. Their story resembles the biblical Fall of Man. I will also prove that Roy is both Satan and Christ, and God can be found on Earth, embodied by Tyrell. To do so I have used a variety of sources(from several books as well as from the internet) and ideas of my own. I divided the thesis into topics each around one literary work. As a conclusion I will try to summarize my achievements, namely how well the works fit into the film and helped to understand the message of Blade Runner.